PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS LABORATORIUM UNTUK MENINGKATKAN HASIL BELAJAR DAN SIKAP ILMIAH SISWA (UPEJ Unnes Physics Education Journal, 2012)
The aims of this research are : (1) to analyze the increase in learning outcomes, (2) to analyze the increase in students' scientific attitude, (3) to analyze changes in scientific attitude of students in the application of learning guided inquiry-based laboratory. Studies using experimental models with pre-post design control group with random sampling. In the analysis of research data is divided into two data analysis before and after the research. From the research results obtained by increasing the gain of 0.53 learning outcomes and increase students' scientific attitude gain of 0.31. So it can be concluded that guided inquiry-based laboratory has a significant influence on the learning outcomes and scientific attitude. Another finding in this study were obtained a relationship, that each increase of scientific attitude will affect the improvement of student learning outcomes.